Laboratory activities, science education and problem-solving skills - Leite, Laurinda (2013)
Science education specialists, science teachers as well as Portuguese science curricula acknowledge lab activities as important educational tools, namely for students to learn how to do science. If doing science is conceptualized as solving problems, some kinds of lab activities may be more appropriate for students to attain that objective than others. This paper presents a categorization of lab activities based on both their main educational goal and the way they deal with phenomena and models. Afterwards, it discusses the extent to which each type of lab activities fosters the development of problem-solving skills.